Functional effects of natural silicate, yeast and saponins based product on the growth and health status of the Pacific white shrimp Litopenaeus vannamei - Novriadi, Romi; Rukmono, Djumbuh; Shapira, Benny; Farzeli, Arik (Indonesian Society of Scientific Aquaculture (ISSA), 2022)
ABSTRACT In this study, a commercial product of natural silicates and yeast (NSY) and saponins from Yucca schidigera and Quillaja saponaria plants (SBP) were used to evaluate their nutritional effects on growth and health status of pacific white shrimp Litopenaeus vannamei. Four isonitrogenous and iso-lipidic experimental diets were formulated to contain 0%, 0.3% NSY, 0.2% SBP and 0.6% NSY. After 60 days, shrimp were sampled and standard haemato-immunological parameters were measured. The growth performances of shrimp were significantly affected by the dietary inclusion of NSY and SBP, whereas the inclusion of NSY and SBP provide a better growth compared to the control group. Additionally, the inclusion of NSY and SBP significantly enhance the total haemocytes count and lysozyme activity in shrimp compared to control. Therefore, NSY and SBP can be regarded as the functional ingredients in shrimp diet to improve the growth and non-specific immune function of shrimp.Keywords: Silicates and yeast, saponins, growth, health status, shrimp Litopenaeus vannamei ABSTRAK Pada kajian ini, produk komersial yang berbasiskan kepada komponen alamiah silikat dan ragi (NSY) dan saponins yang berasal dari tumbuhan Yucca schidigera dan Quillaja saponaria (SBP) digunakan untuk mengevaluasi pengaruhu nutrisi yang dimiliki terhadap pertumbuhan dan status kesehatan dari udang putih Litopenaeus vannamei. Empat pakan yang bersifat iso-nitrogen dan iso-lipid diformulasikan dengan perlakuan 0%, 0.3% NSY, 0.2% SBP and 0.6% NSY. Setelah 60 hari, udang kemudian diambil sampelnya dan protokol standard untuk uji hemato-immunologi dilakukan. Laju pertumbuhan udang secara signifikan dipengaruhi oleh keberadaan NSY dan SBP, dimana inklusi NSY dan SBP memberikan pertumbuhan yang lebih baik dibandingkan kontrol. Selain itu, penggunaan NSY dan SBP secara signifikan meningkatkan jumlah total hemosit dan aktivitas lisozim pada udang perlakuan dibandingkan kontrol. Oleh karena itu, NSY dan SBP dapat digolongkan sebagai bahan baku fungsional pada pakan udang untuk meningkatkan pertumbuhan dan fungsi imun non-spesifik pada udangKata kunci: Silikat dan ragi, saponins, laju pertumbuhan, status kesehatan, udang Litopenaeus vannamei